Monetary policy interdependency in fisher effect: A comparative evidence - Olatunji Abdul Shobande; Oladimeji Tomiwa Shodipe (Journal of Central Banking Theory and Practice, 2021)
In this paper, we examine the ability of Fisher effect to describe the subjective behaviour of monetary policy responses for nations constrained by global factors. We developed and estimated a simple DSGE model for appraising the consequence of an integrated financial market predictor on national monetary policy response in Africa's largest economies - Nigeria and South Africa. The paper integrated the theoretical intuition of the famous Fisher effect on the New Keynesian DSGE model with global predictors to describe national monetary policy response as it influence domestic financial variables and macroeconomic fundamentals. Simulations show that the existence of global factors threatens the abilities of national monetary policy to predict financial variables and macroeconomic fundamentals in their economies.
Keywords: D50; C53; E12; E44; E61; 330; DSGE model; Macroeconomic forecast; Monetary policy; Fisher effect; Africa